2013
DOI: 10.1002/hep.26618
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of FOXO3 by phosphorylation and methylation in hepatitis C virus infection and alcohol exposure

Abstract: Hepatitis C infection produces chronic liver injury that is significantly exacerbated by alcohol consumption. While multiple mechanisms contribute to this synergy, a viral-induced loss of antioxidant responses has been shown to play an important role. This study examined the effects of HCV infection and alcohol on the regulation of the transcription factor FOXO3, an important regulator of SOD2 expression, a tumor suppressor, and a component of the hepatic antioxidant response system. FOXO3 was activated by eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 29 publications
4
51
0
Order By: Relevance
“…The discovery that p-574-FOXO3 is a specifically pro-apoptotic form of the protein is thus an important advance in our understanding of FOXO3. S-574 was first reported to be a site of FOXO3 phosphorylation by Brunet et al 17 We previously observed this phosphorylated form after HCV infection 23 and now have determined that it occurs after EtOH treatment of hepatocytes or LPS treatment of macrophages as well. We were able to demonstrate a strong connection between JNK activation and the appearance of p-574-FOXO3 as it was induced by activated JNK1 expression, its formation was blocked by JNK inhibitor and the time course of its appearance closely followed that of JNK activation for either LPS-treated macrophages or alcohol-treated hepatoma cells (Supplementary Figure S2).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…The discovery that p-574-FOXO3 is a specifically pro-apoptotic form of the protein is thus an important advance in our understanding of FOXO3. S-574 was first reported to be a site of FOXO3 phosphorylation by Brunet et al 17 We previously observed this phosphorylated form after HCV infection 23 and now have determined that it occurs after EtOH treatment of hepatocytes or LPS treatment of macrophages as well. We were able to demonstrate a strong connection between JNK activation and the appearance of p-574-FOXO3 as it was induced by activated JNK1 expression, its formation was blocked by JNK inhibitor and the time course of its appearance closely followed that of JNK activation for either LPS-treated macrophages or alcohol-treated hepatoma cells (Supplementary Figure S2).…”
Section: Discussionmentioning
confidence: 80%
“…32 They were chosen for this study as previous isoelectric focusing studies showed that HCV infection and alcohol generated specific and different FOXO3 PTMs and these appeared to determine antioxidant responses. 23 In this earlier study we observed that HCV caused a specific species of FOXO3 that contained S-574 phosphorylation but this particular species was not identified after EtOH treatment. This implies that the HCVinduced and EtOH-induced p-574 phosphorylated forms of FOXO3 may differ at other sites as they have different pIs.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…It is likely that an ethanol-induced FOXO3 post-translational modification change makes it a better substrate for Akt phosphorylation. Recent studies from our laboratory have shown that the combination of HCV and alcohol specifically suppresses arginine methylation of FOXO3, 47 and this is expected to make it a better substrate for Akt phosphorylation, causing nuclear export and degradation. 48 Because the effects can be seen in our transgenic mice and infected cells, the HCV structural proteins, particularly core, may play a critical role in FOXO3 modulation.…”
Section: Discussionmentioning
confidence: 99%